Solar integration: applying hybrid photovoltaic/thermal systems - Williams, Kristen (Kansas State University, 2010)
On-site energy production is becoming increasingly prevalent in building systems design with a renewed public awareness of sustainability, decreased energy resources, and an increase in the requirements of local and federal energy codes. Systems such as photovoltaics and solar thermal collectors have been implemented in designs to meet these challenges. The emerging technology of hybrid photovoltaic thermal (PVT) offers the potential to combine these systems into one contained module. A hybrid PVT system can simultaneously produce thermal and electrical energy, maximizing the use of available surface area available for energy production. Hybrid PVT can be implemented using PVT air collectors, PVT liquid collectors, and ventilated PV facades. Hybrid PVT is gaining interest at the academic level and is being applied at the residential level. Several commercial hybrid PVT products are currently manufactured, but options are limited. This report will evaluate PV, solar thermal collector, and hybrid PVT technologies, discuss the various components required for these systems, and present advantages and disadvantages of these systems. For an example elementary school design, the report will compare monthly energy production of the various systems, evaluating their ability to supply the peak loads of an example building design. Estimated first costs and operating and maintenance costs will be evaluated. The report will also quantify the ideal balance of PV and solar thermal collectors for the example based on loads and simple payback. Conclusions will be made about the current state of hybrid PVT and what steps need to be taken for it to be effectively implemented in the commercial building market.
Keywords: Hybrid; Photovoltaic; Thermal; Collector; Solar; Engineering, General (0537)